NELAYAN BIJAK, LAUT BERKELANJUTAN: EDUKASI PENGELOLAAN KEUANGAN SEDERHANA DAN EKONOMI BIRU BAGI KOMUNITAS PESISIR KELOMPOK NELAYAN POLE MAUPA - Indra Basir; Muhammad Ihsan Ansari; Nur Fitriani (Jurnal Abdi Insani, 2026)
This community service program aims to enhance financial literacy and strengthen blue economy awareness as a foundation for sustainable economic development among the Pole Maupa fishermen community in Majene, West Sulawesi. The program seeks to improve basic financial recording skills, strengthen collective financial management, and increase awareness of sustainable fishing practices and value-added product diversification. The activities included socialization, financial recording training using a pocketbook, blue economy education, and training on fish-based product diversification. Evaluation was conducted using pre-test and post-test instruments consisting of 6 items on financial literacy and 5 items on blue economy and product diversification. A participatory approach was applied with active involvement of lecturers and students. Post-test results indicated a substantial improvement: 100% of participants were able to record cash flow, 85% separated household and business finances, and 90% participated in collective fund management. In terms of blue economy outcomes, 90% understood the blue economy concept, 95% demonstrated awareness of coastal ecosystem protection, and 100% committed to avoiding destructive fishing gear. Additionally, 90% showed interest in developing value-added products such as fish floss and smoked fish. Financial literacy gains also reduced reliance on informal lenders, decreasing from 75% to 35%. The program effectively improved the economic and ecological capacity of fishermen and strengthened collaboration between the community and the university. These results highlight the importance of local institutional support in sustaining coastal community empowerment.